Serat Suluk babaraning Ngelmi Makrifat Wasiyat Kala Kanjeng Nabi Kilir - Saddhono, Kundharu Saddhono (AL-TAHRIR, 2013)
Abstract: Suluk (mysticism or sufism) is a mystical world that isvery personal in terms of peace of mind and spiritual needs. Inshort, mysticism can be defined as the love of the Absolute (divine).Material object in this study is a single manuscript titled SeratSuluk Babaring Ngelmi Makripat Wasiat Kala Kanjeng Nabi Kilir(SSBM), the literature describes the knowledge of the ProphetKilir makrifat legacy (read: Khidhr) to Sunan Kalijaga or SyekhMelaya. Khidhr was a prophet who told in the Qur’an (al-Kahfi:60-82). In this study, researcher focused on two things: attitudesin SSBM and their relevance for society in the modern era. Thisresearch is a form of qualitative research that concentrates on theanalysis of text. Reading of the text is done in two ways: heuristicsand hermeneutics. The results showed that the fibers text SSBM anuanced Islamic religious literature belonging to Java popular.However, the expertise of the poets of the past in working-knowledgeliterature making such knowledge in a kind of text into knowledgethat seems real local wisdom and Java knowledge is not just theresult of acculturation.